The cultural identity of foragers and the Agta of Palanan, Isabela, the Philippines - Griffin, Marcus B. (Anthropos Institute, 1996)
This paper examines the agency foragers may have in determining their cultural identity and social organization using the example of the Agta of eastern Luzon, Philippines. The use of political economic theory in many studies of foragers has overemphasized the significance of economic exchange between foragers and farmers or pastoralists at the expense of political negotiation(s) and the sociological meaning(s) of economic interaction. The issue of agency is significant because foragers, as in the Agta case, must increasingly contend with state intrusions in the form of wildlife sanctuaries, national parks, and tourism.